Visualizing Basic Accounting Flows: Does XBRL + Model + Animation = Understanding? - Marshall,Byron; Mortenson,Kristian; Bourne,Amy; Price,Kevin (International Journal of Digital Accounting Research, 2010)
The usefulness of XBRL (eXtensible Business Reporting Language) in facilitating efficient data sharing is clear, but widespread use of XBRL also promises to support more effective analysis processes. This format should allow managers, investors, regulators, and students to aggregate, compare and analyze financial information. This study explores an XBRL-based visualization tool that maps the organization of financial statements captured in the XBRL formalism into a graphical representation that organizes, depicts, and animates financial data. We show that our tool integrates and presents profitability, liquidity, financing, and market value data in a manner recognizable to business students. Our findings suggest the promise of XBRL-based visualization tools both in helping students grasp basic accounting concepts and in facilitating financial analysis in general.
Keywords: Accounting; BIS